Bottlenecks in organizing the workflows of large HPC centers - Nikitenko, Dmitry A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2023)
Effective output from data centers are determined by many complementary factors. Often, attention is paid to only a few, at first glance, the most significant of them. For example, this is the efficiency of the scheduler, the efficiency of resource utilization by user tasks. At the same time, a more general view of the problem is often missed: the level at which the interconnection of work processes in the HPC center is determined, the organization of effective work as a whole. missions at this stage can negate any subtle optimizations at a low level. This paper provides a scheme for describing workflows in the supercomputer center and analyzes the experience of large HPC facilities in identifying the bottlenecks in this chain. A software implementation option that gives the possibility of optimizing the organization of work at all stages is also proposed in the form of a support system for the functioning of the HPC site.